Diagnostic and Treatment Challenges of Sighted Non–24-Hour Sleep-Wake Disorder - Malkani, Roneil G. (J Clin Sleep Med, 2018)
STUDY OBJECTIVES: To report the diagnostic and treatment challenges of sighted non–24-hour sleep-wake disorder (N24SWD). METHODS: We report a series of seven sighted patients with N24SWD clinically evaluated by history and sleep diaries, and when available wrist actigraphy and salivary melatonin levels, and treated with timed melatonin and bright light therapy. RESULTS: Most patients had a history of a delayed sleep-wake pattern prior to developing N24SWD. The typical sleep-wake pattern of N24SWD was seen in the sleep diaries (and in actigraphy when available) in all patients with a daily delay in midpoint of sleep ranging 0.8 to 1.8 hours. Salivary dim light melatonin onset (DLMO) was evaluated in four patients but was missed in one. The estimated phase angle from DLMO to sleep onset ranged from 5.25 to 9 hours. All six patients who attempted timed melatonin and bright light therapy were able to entrain their sleep-wake schedules. Entrainment occurred at a late circadian phase, possibly related to the late timing of melatonin administration, though the patients often preferred late sleep times. Most did not continue treatment and continued to have a non–24-hour sleep-wake pattern. CONCLUSIONS: N24SWD is a chronic debilitating disorder that is often overlooked in sighted people and can be challenging to diagnose and treat. Tools to assess circadian pattern and timing can be effectively applied to aid the diagnosis. The progressive delay of the circadian rhythm poses a challenge for determining the most effective timing for melatonin and bright light therapies. Furthermore, once the circadian sleep-wake rhythm is entrained, long-term effectiveness is limited because of the behavioral and environmental structure that is required to maintain stable entrainment. CITATION: Malkani RG, Abbott SM, Reid KJ, Zee PC. Diagnostic and treatment challenges of sighted non–24-hour sleep-wake disorder. J Clin Sleep Med. 2018;14(4):603–613.